Interactive e-learning environment to printed circuit board design - Chai, Jia Zhe (Nanyang Technological University, 2024)
Printed circuit boards (PCBs) are essential devices for electronic engineering and design. However, learning how to create and test PCBs can be challenging and costly for beginners. This project aims to develop an interactive e-learning environment that can teach the basics of PCB creation and simulation using a web-based platform. This project is not intended to be an exhaustive approach to teaching, but instead it will allow learners to quickly turn their basic circuits into PCBs while gaining experience with the creation tools.